1976
DOI: 10.1126/science.194.4271.1288
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogic and Petrologic Implications of Viking Geochemical Results From Mars: Interim Report

Abstract: Chemical results from four samples of martian fines delivered to Viking landers 1 and 2 are remarkably similar in that they all have high iron; moderate magnesium, calcium, and sulfur; low aluminum; and apparently very low alkalies and trace elements. This composition is best interpreted as representing the weathering products of mafic igneous rocks. A mineralogic model, derived from computer mixing studies and laboratory analog preparations, suggests that Mars fines could be an intimate mixture of about 80 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(61 citation statements)
references
References 14 publications
1
60
0
Order By: Relevance
“…The iron content in the soil of Mars was determined by x-ray fluorescence spectroscopy, and based on this it was inferred that Fe 2 O 3 composes Ϸ19% of the soil at both Viking landing sites (25). Our thermodynamic analysis shows that at the Viking temperatures (200-500°C), the reduction of hematite (Fe 2 O 3 ) by hydrogen is thermodynamically favored; however, in the gas phase the dissociation of molecular hydrogen to atomic hydrogen (a necessary step to cause the reaction) is extremely slow at temperatures of Ͻ1,500°C (26).…”
Section: Resultsmentioning
confidence: 99%
“…The iron content in the soil of Mars was determined by x-ray fluorescence spectroscopy, and based on this it was inferred that Fe 2 O 3 composes Ϸ19% of the soil at both Viking landing sites (25). Our thermodynamic analysis shows that at the Viking temperatures (200-500°C), the reduction of hematite (Fe 2 O 3 ) by hydrogen is thermodynamically favored; however, in the gas phase the dissociation of molecular hydrogen to atomic hydrogen (a necessary step to cause the reaction) is extremely slow at temperatures of Ͻ1,500°C (26).…”
Section: Resultsmentioning
confidence: 99%
“…However, as is evident from Table 1, Scooby Doo-except for SO 3 , Cl, and MgO-falls within the compositional range of the analyzed rock samples. This observation suggests that sedimentary rocks could form from soils at the Pathfinder landing site.…”
mentioning
confidence: 90%
“…Although the two landing sites of Viking 1 and Viking 2 were about 6500 km apart from each other, the composition of the soils analyzed at both sites was rather similar and was interpreted to represent the weathering products of mafic igneous rocks (3). In particular, it was suggested that sulfur and chlorine were introduced by the interaction of volcanic gases with the mafic surface material, forming sulfates and chlorides (4,5).…”
mentioning
confidence: 99%
“…Baird et al (1976Baird et al ( , 1977, Toulmin et al (1977), and Gooding (1992) found that the composition of the Viking soils could be matched with multicomponent models including hydrous alteration phases, such as smectites. Clark (1993) pointed out that the palagonite model is actually a variant of the smectite model but with poorer crystallinity.…”
Section: Implications For Marsmentioning
confidence: 99%